Improvement of fermented milk desserts using secondary dairy raw materials - Osmak, Anton; Bandura (Kuzmyk), Uliana; Bass, Oksana (My University, 2025)
he need to create functional dessert products with the introduction of secondary resources is relevant. First, the original formulations for dairy desserts are rarely used. The production of non-traditional types of desserts, such as multi-component dessert products, has no analogs on the market yet. Second, the use of whey as a raw material is relevant due to the current shortage of milk worldwide.
Keywords: whey; dessert; десерт багатокомпонентний; кафедра технології молока і молочних продуктів; сироватка молочна